USING NoSQL DATABASE - FIREBASE IN REAL-TIME SYSTEMS BASED ON CLIENT SERVER TECHNOLOGY (Scientific journal of the Fergana State University, 2023)
Nowadays we use different real-time systems based mobile applications for teaching, reading, listening, watching and data processing. Firebase real-time NoSQL database from company Google. We can use this database with our real-time systems based on client server technology Flutter cross platform application. It is secure, fast, have own real-time notification system. Without this Firebase easy and excellent for integration with Flutter application and have, own cloud system.